2014
DOI: 10.1021/jm500409k
|View full text |Cite
|
Sign up to set email alerts
|

Saccharin Derivatives as Inhibitors of Interferon-Mediated Inflammation

Abstract: A series of novel, saccharin-based antagonists have been identified for the interferon signaling pathway. Through in vitro high-throughput screening with the Colorado Center for Drug Discovery (C2D2) Pilot Library, we identified hit compound 1, which was the basis for extensive structure–activity relationship studies. Our efforts produced a lead anti-inflammatory compound, tert-butyl N-(furan-2-ylmethyl)-N-{4-[(1,1,3-trioxo-2,3-dihydro-1λ6,2-benzothiazol-2-yl)methyl]benzoyl}carbamate CU-CPD103 (103), as a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…Others have reported that RAW 264.7 cells lack a functional TLR5 (Means et al, 2003). We probed the activating effect of TLR ligands along with HMGB1 in RAW 264.7 cells by performing a NO assay as previously described (Csakai et al, 2014). HMGB1 significantly activated the NF-κB-driven inducible NO synthase (iNOS) gene in comparison to other TLR ligands such as PAM2 (TLR2), LPS (TLR4) and the RAGE ligand AGE-BSA (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have reported that RAW 264.7 cells lack a functional TLR5 (Means et al, 2003). We probed the activating effect of TLR ligands along with HMGB1 in RAW 264.7 cells by performing a NO assay as previously described (Csakai et al, 2014). HMGB1 significantly activated the NF-κB-driven inducible NO synthase (iNOS) gene in comparison to other TLR ligands such as PAM2 (TLR2), LPS (TLR4) and the RAGE ligand AGE-BSA (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…We employed a previously reported nitric oxide (NO) assay (Csakai et al, 2014) on primary rat PBMCs. Treatment of the PBMCs with flagellin and HMGB1 resulted in significant production of NO that was decreased upon TH1020 treatment at 0.75 and 1.5 µM (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is predicted that overall hydrophobicity of active site residues can also play a role in SAC active site entry hence the observed difference in binding between CA IX and CA XII 12 . It has previously been shown that SAC can be u se d as a lead group for CA inhibitor design 19,31 . However until now, there was no structural information available as to how the tail regions of these compounds interact with the CA active site.…”
Section: Discussionmentioning
confidence: 99%
“…Yin et al identified a series of saccharin‐based antagonists for the interferon signaling pathway. The lead anti‐inflammatory compound, tert ‐butyl N ‐(furan‐2‐ylmethyl)‐ N ‐{4‐[(1,1,3‐trioxo‐2,3‐dihydro‐1λ 6 ,2‐benzothiazol‐2‐yl)methyl]benzoyl}carbamate ( 103 ), acts as a potent inhibitor in an established nitric oxide (NO) signaling assay . Benzosultam 104 acted as a lead compound for both general and partial epileptic seizures in minute levels …”
Section: Use Of Sultams In Biological Fieldsmentioning
confidence: 99%
“…The lead anti-inflammatory compound, tert-butyl N-(furan-2-ylmethyl)-N-{4-[(1,1,3-trioxo-2,3-dihydro-1λ 6 ,2-benzothiazol-2-yl)methyl]benzoyl}carbamate (103), acts as a potent inhibitor in an established nitric oxide (NO) signaling assay. [85] Benzosultam 104 acted as a lead compound for both general and partial epileptic seizures in minute levels. [86] Fauber and co-workers engineered compound 105, which possessed potent, selective, and orally bioavailable retinoic acid receptor-related orphan receptor C (RORc) inverse agonist potency in a cell assay with no distinguishable activity against any of the other RORs or NRs in the small cell panel.…”
Section: Use Of Sultams In Biological Fieldsmentioning
confidence: 99%